THE USE OF 3-2-1 STRATEGY IN TEACHING READING COMPREHENSION ON REPORT TEXT - Jauhari, Marlia Purnama; Arifin, Zainal; Fergina, Ana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: The 3-2-1 strategy is a reading strategy that requires students’ participation on summarizing ideas from the text, encourages them to think independently, and invites them to engage with the text. The aim of this research was to investigated whether the 3-2-1 strategy increased students’ achievement in reading comprehension on report text. Reading comprehension is the process of simultaneously extracting meaning through interaction and involvement with written language. Report text is a text presenting information about something like social phenomena in our environment. The research method used a pre-experimental research. The population of the ninth grade students of SMP Pertiwi Pontianak in academic year 2015/2016 consisted of 26 students and sample consisted of 24 students. The data was calculated and the result showed that the mean score of pre-test was 5.63 and post-test was 7.77. There was significant difference of students mean score in reading comprehension on report text between pre-test and post-test after treatment. The 3-2-1 strategy can be applied in teaching learning process to increasing the knowledge of reading text. Keyword: The 3-2-1 Strategy, Reading Comprehension, Report Text Abstrak: Penelitian in menggunakan strategi 3-2-1 dalam pemahaman mengajar membaca teks report. Tujuan penelitian ini untuk meneliti apakah strategi 3-2-1 meningkatkan pencapaian siswa dalam pemahaman membaca teks report. Pemahaman membaca adalah proses menyaring makna melalui interaksi dan keterlibatan dengan penulisan bahasa. Teks report adalah jenis teks yang mempresentasikan informasi tentang sesuatu seperti fenomena sosial di lingkungan kita. Metode penelitian tersebut menggunakan pre-eksperimental. Populasi  siswa kelas IX SMP Pertiwi Pontianak tahun akademik 2015/2016 yaitu 26  siswa dan sampel siswa kelas IX tersebut yaitu 24 siswa. Hasil dan jumlah data tersebut dapat dilihat dari nilai rata-rata pre-test yaitu 5,63 dan nilai post-test yaitu 7,77. Terdapat perbedaan yang sangat signifikan antara hasil pre-test dan post-test setelah perlakuan pada nilai rata-rata siswa dalam mengajar pemahaman membaca teks report. Strategi 3-2-1 dapat diterapkan di dalam proses belajar mengajaruntuk meningkatkan pengetahuan membaca teks. Kata Kunci: Strategi 3-2-1, Pemahaman Membaca, Teks Report